A perpétua tensão da consciência: o conceito de revolta e seus deslocamentos - Ribeiro, Rafael Lins (2021)
In our work, we seek to demonstrate the emergence of the feeling of revolt in The Myth of Sisyphus, by Albert Camus, as well as its metaphysical unfolding and its variations in meaning in The Rebel: An Essay on Man in Revolt, by the same author. Enunciating revolt as an attitude of tension in the clash between the human being and the world, we examine this concept, addressing its unfolding within the horizon of Camusian thought. Following the lines of the philosopher's reasoning, starting with the rejection of suicide, our research also proposes to think of revolt as an authentic way for human beings to deal with the absurd, admitting the truth and responsibility for existence, without escapism, leaps of faith or fanaticism, in the search for the missing piece of the puzzle of the human condition.